Prognostic model construction and validation of esophageal cancer cellular senescence-related genes and correlation with immune infiltration - Zheng, Shiyao; Lin, Nan; Wu, Qing; He, Hongxin; Yang, Chunkang (Frontiers in Surgery, 2023)
Cellular senescence is a cellular response to stress, including the activation of oncogenes, and is characterized by irreversible proliferation arrest. Restricted studies have provided a relationship between cellular senescence and immunotherapy for esophageal cancer. In the present study, CS-related differentially expressed genes were initially screened from TCGA-ESCA. Five CS-associated prognostic genes were identified by WGCNA, COX, and lasso regression analysis, including H3C1, IGFBP1, MT1E, SOX5 and CDHR4, and a CS-related risk score (CSRS) was calculated. We constructed a prognostic model based on CSRS, which was validated well in an independent cohort, GSE53625. The nomogram model predicts better clinical benefit than the American Joint Committee on Cancer (AJCC) staging for prognosis of patients with esophageal cancer with a five-year AUC of 0.946. Patients with high CSRS had a poor prognosis (HR=2.93, 95%CI=1.74-4.94, p<0.001). We observed differences in the distribution of CSRS in different pathological staging and therefore performed a subgroup survival analysis finding that assessment of prognosis by CSRS independent of pathological staging. Comprehensive immune infiltration analysis and functional enrichment analysis suggested that patients with high CSRS may develop immunotherapy resistance through mechanisms of deacetylation and methylation. In summary, our study suggested that CSRS is a prognostic risk factor for esophageal cancer. Patients with high CSRS may have worse immunotherapy outcomes.